2008
DOI: 10.1111/j.1728-4465.2008.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Policies and Practices Concerning Normal Childbirth in Jordan

Abstract: In Europe and North America, movements have long been established to make childbirth safer for the mother and the newborn and more responsive to the needs of individual women. In particular, women's groups have resisted the medicalization of childbirth and have argued that childbirth is a normal and important event in women's lives, and that women should make birthrelated decisions in partnership with health-care providers. Therefore, professional expectations and regulatory mechanisms to conform to the standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…These findings support an earlier study carried out in Jordan in which the majority of hospitals reported having written policies regarding childbirth, breastfeeding and the care of mothers (Sweidan et al, 2008). In contrast, the majority of Syrian and Lebanese hospitals studied did not have written childbirth policies (Khayat and Campbell, 2000;Abdulsalam et al 2004).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These findings support an earlier study carried out in Jordan in which the majority of hospitals reported having written policies regarding childbirth, breastfeeding and the care of mothers (Sweidan et al, 2008). In contrast, the majority of Syrian and Lebanese hospitals studied did not have written childbirth policies (Khayat and Campbell, 2000;Abdulsalam et al 2004).…”
Section: Discussionsupporting
confidence: 85%
“…Enemas were found to be given routinely in around 45% of the hospitals. A similarly high rate (67%) was found in Jordanian hospitals (Sweidan et al, 2008). Enemas cause discomfort and embarrassment for women during labour.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations